SOLUBILITY ENHANCEMENT OF ATORVASTATIN USING SOLID DISPERSION TECHNIQUE WITH POLOXAMERS. (International Journal of Food and Nutritional Sciences, 2026)
ABSTRACTObjective: This study aims to enhance solubility and dissolution rate of a BCS class II drug atorvastatin by formulating it into solid dispersion using poloxamer 188 and poloxamer 407.Method: Solid dispersions were prepared using Melt dispersion and solvent evaporation techniques based on 2^2 factorial design. Drug excipient compatibility was studied using FTIR. The prepared formulations were characterized for flow properties, saturation solubility, crystalline behaviour (X ray diffraction), and in vitro dissolution performance.Results: Compatibility studies performed show no significant interactions between drug and excipients and X-ray diffraction analysis indicated a reduction in the crystallinity of atorvastatin in the solid dispersion form. Saturation solubility and dissolution studies showed a significant increase in drug solubility and dissolution rate compared with the pure drug. Among all formulations, solid dispersions prepared with Poloxamer 188 with 1:0.8 drug ratio by the solvent evaporation method showed the highest improvement in aqueous solubility of 3.362± 0.024. Conclusion: the formulated solid dispersion with poloxamers have showed increased solubility then upon further increase in concentration of poloxamers the solubility has slightly decreased this might be because of the hydrophobic nature of carrier at high concentration this can be further utilized for development of efficient oral drug delivery system.